Perforated sarcomatoid carcinoma of the jejunum: Case report - HAN, NING (D.A. Spandidos, 2013)
Sarcomatoid carcinomas exhibit features that are common to epithelial and mesenchymal tumors. These carcinomas are rare, particularly in the small intestine. In the current case report, we describe a case of an intestinal sarcomatoid carcinoma in a 70-year-old Chinese female. Sarcomatoid carcinoma was confirmed based on light microscopy and immunohistochemical observations. The patient presented with symptoms of acute abdomen, which was due to an intestinal perforation caused by sarcomatoid carcinoma of the small bowel. Patients with sarcomatoid carcinoma are usually associated with a poor prognosis. However, this patient experienced a relatively favorable prognosis, which may be attributed to low positivity for Ki67 in the tumor.